Analisa Perencanaan Lumpur Pemboran Menggunakan HPWBM pada Sumur “E” Lapangan “P” - Prastio, Eko (Jurnal Jaring SainTek, 2022)
The “E” well to be drilled is a development well in the “P” field located in the North Sumatra Basin. During the drilling operation in well “E” using HPWBM, HPWBM is used to overcome shale instability. This water-based mud is used because it is cheaper and more economical than using oil-based mud. However, this mud needs to be added with other chemicals because HPWBM has a weakness in controlling shale formation. The mud system design for the “E” well uses the offset well method, which uses data from nearby wells for comparison. Well “E” is divided into two intervals. Hole interval 12 1/4" with 9 5/8" casing from 24 m to 290 m depth using HPWBM. Then proceed with 8 1/2" hole intervals with 7" casing from 290 m to 530 m depth using the same mud. The problem this well will face is pressure at a depth of 500 m, thus increasing the mud density from 12 ppg to 14 ppg to prevent kick.